Evaluation of the association between asthma and non-neurogenic urinary incontinence in children; a case-control study - Elaheh Ziaei; Fatemeh Dorreh; Parsa Yousefichaijan; Roham Sarmadian; Nooshin Sajjadi; Manijeh Kahbazi (BMC, 2023)
Abstract Background Asthma is the most common chronic disease in children. Asthma can lead to sleep disorders and psychiatric issues, which are often accompanied by urinary incontinence in children. Furthermore, several studies have shown a relationship between allergic diseases and urinary incontinence. This study aims to examine the association between asthma and non-neurogenic urinary incontinence. Materials and methods This case-control study included 314 children over three years old referred to Amir Kabir Hospital; 157 with asthma and 157 without asthma. After explaining each urinary disorder in accordace with the International Children's Continence Society's definitions, parents and children were asked about their presence. The disorders included monosymptomatic nocturnal enuresis(MNE), nonmonosymptomatic nocturnal enuresis (NMNE), vaginal reflux (VR), pollakiuria, infrequent voiding, giggle incontinence (GI), and overactive bladder (OAB). The analysis was performed using Stata 16. Results The average age of the children was 8.19 ± 3.15 years. Patients with asthma (p = 0.0001) and GI (p = 0.027) had a considerably lower average age than patients without these disorders. Asthma and urinary incontinence, including NMNE, Infrequent voiding, and OAB, were significantly correlated (p = 0.017, 0.013, and 0.0001, respectively). Moreover, the association between MNE and asthma was significant in males (p = 0.047). Conclusion Due to the relationship between asthma and urinary incontinence, children with asthma must be evaluated for the presence of urinary disorders and, if present, receive the proper treatment in order to improve their quality of life.